Mce4F Mycobacterium tuberculosis protein peptides can inhibit invasion of human cell lines (2015)
This work was aimed at studying the Mycobacterium tuberculosis H37Rv Rv3494c protein, taking into account that it belongs to the mammalian cell entry family (mce) which is thought to have important functions in the disease's pathogenesis. The protein was characterized in silico; its presence on mycobacterial surface was confirmed by immunoelectron microscopy. High-activity binding peptides (HABPs) were identified by binding assays with 125I; their ability to inhibit mycobacterial entry to two cell lines (U937 alveolar macrophages and A549 epithelial cells) was ascertained and their role in bacterial entry was confirmed by fluorescent microsphere internalization assay. This protein's predicted alpha-helix structure was confirmed by circular dichroism of its peptides. All HABPs inhibited mycobacterial entry to cells and that the 38379 peptide (201IDQAGPFLQAQIRAGGDIKSY220) had high binding ability and inhibited the mycobacterial entry to both cell lines assayed here. Rv3494c peptides 38370 (21LSVMAIFYLRLPATFGIGTY40), 38373 (81HMRLNSGTAIPSNVTATVRSY100) and 38379 (201IDQAGPFLQAQIRAGGDIKSY220) showed to be HABP and inhibited mycobacterial entry to A549 cells and peptide 38382 (261RPSFPALAASLANLGRVGVIY280) bind to U937 and inhibited the mycobacterial entry to this cell line; all of these sequences play an important role in cell line recognition and invasion, and may thus be considered in the search for prophylactic candidates against tuberculosis. © FEMS 2015.